2017
DOI: 10.1002/2016jc012597
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sea level rise on tidal range in Chesapeake and Delaware Bays

Abstract: Coastal inundation is affected not only by rising mean sea level but also by changing tides. A numerical model is developed to investigate how sea level rise and coastline changes may impact tides in two coastal‐plain estuaries, Chesapeake Bay and Delaware Bay. Despite their different tidal characteristics, the two estuaries display similar responses to the sea level rise and shoreline management scenarios. When hypothetic sea walls are erected at the present coastline to prevent low‐lying land from flooding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 55 publications
(98 reference statements)
12
133
1
Order By: Relevance
“…The modelling results of hydrodynamic response to SLR for Lake Illawarra and the Shoalhaven Estuary match well with recent studies by Lee et al [12] and Du et al [13]. Both studies suggested that tidal ranges may increase in those estuaries that are characterised by steep channel banks and that tidal ranges may remain unchanged or even decrease in estuaries that are characterised by broad floodplains, which may act as a sink for tidal energy.…”
Section: Hydrodynamic Response To Slrsupporting
confidence: 78%
See 2 more Smart Citations
“…The modelling results of hydrodynamic response to SLR for Lake Illawarra and the Shoalhaven Estuary match well with recent studies by Lee et al [12] and Du et al [13]. Both studies suggested that tidal ranges may increase in those estuaries that are characterised by steep channel banks and that tidal ranges may remain unchanged or even decrease in estuaries that are characterised by broad floodplains, which may act as a sink for tidal energy.…”
Section: Hydrodynamic Response To Slrsupporting
confidence: 78%
“…Their simulations suggest that average water depth in inundated areas increases linearly with SLR, but at a slower rate than on the open coast, while average salinity in inundated areas increases linearly with SLR. Lee et al [12] investigated tidal response to SLR in two coastal-plain estuaries in the USA, Chesapeake Bay and Delaware Bay, using the unstructured-grid finite volume Coastal ocean model (FVCOM) and hypothetical adaptation options (sea walls). Their simulations indicate a non-linear tidal response to SLR and a reduction in tidal range in up-stream locations due to tidal energy dissipation through inundation of low-lying areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the mid‐21st century, GCM projections for the Northwest Atlantic Ocean were used to prescribe changes in the offshore boundary condition for ROMS‐RCA. The relative sea level rise was set to be the sum of the CMIP3 sea level projection for the region (Mitrovica et al, ; Mitrovica et al, ; Slangen et al, ) and the local sea level rise due to land subsidence (Miller et al, ; Zervas, ), following Boesch et al () and Lee et al (; Table ). To set the temperature condition, we calculated the difference of monthly mean water temperature between 1971–2000 and 2041–2070 from the GCM outputs and added this difference to the historical climatology (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, the rates of tidal level changes observed are of similar magnitudes to the rate of mean sea level (MSL) rise at some sites; for example, Mawdsley et al () found increases in tidal range at Astoria (USA), Wilmington (USA), Delfzijl (the Netherlands), Cuxhaven (Germany), and Calais (France) of >25 cm over the last century. Furthermore, a number of modeling studies at local (e.g., Chernetsky et al, ; Familkhalili & Talke, ; Holleman & Stacey, ; Lee et al, ; Orton et al, ), regional (e.g., Arns et al, , ; Devlin et al, ; Greenberg et al, ; Idier et al, ; Luz Clara et al, ; Pickering et al, ; Pelling, Green, et al, ; Pelling, Uehara, et al, ; Ross et al, ; Ward et al, ), and global scales (e.g., Müller et al, ; Pickering, ; Pickering et al, ; Schindelegger et al, ; Wilmes et al, ) confirm that altered conditions (e.g., MSL, bathymetry, or stratification) affect tide levels and currents. Moving forward, these studies suggest that further changes to tidal levels and currents due to nonastronomical causes are possible over the 21st century and beyond.…”
Section: Introductionmentioning
confidence: 99%